Vistas in disease management in ornamental horticulture - Shivakumar, K V; Prabha, K; Madhavan , S; T, Sirisha (Indian Horticulture, 2024)
Ornamental horticulture, focused on the aesthetic cultivation of plants, faces significant challenges due to various plant pathogens, particularly fungi, which can severely impact yield and quality. This article explores Integrated Plant Disease Management (IDM), highlighting key methods such as sanitation, seed treatment, use of biocontrol agents, disease-resistant varieties, and chemical treatments. Emphasizing sustainability, IDM balances traditional and modern approaches to protect ornamental crops, ensuring healthier and more profitable production amidst pathogen threats.